МИСИЈАТА НА АПОСТОЛОТ ПАВЛЕ КАКО ПОЧЕТОК НА ХРИСТИЈАНСТВОТО ВО МАКЕДОНИЈА (Filološke studije, 2019)
The beginning of Christianity in Macedonia was in the middle of 1st century. It’s dedicated to Apostle Paul’s missionary. The New Testament scripts proclaimed that Paul was the first Christian missionary who, in the 50’s of the first century AD, came to Macedonia, preaching. He was in Macedonia three times converting a large number of Macedonian population to Christianity. Lydia was the first woman in Macedonia that accepted the Christian faith. In the following period, Paul’s mission had a big success in every Macedonian city he visited. Due to his mission, there were Christian municipalities created in several Macedonian cities: Philippi, Salonica and Beroia. Those are, however, the first Christian municipalities in Europe which, in a short period of time, grew into powerful communities not only in Macedonia, but much farther away.